Coordination-Induced Self-Assembly of a Heteroleptic Paddlewheel-Type Dirhodium Complex - Kazuki Arakawa; Natsumi Yano; Nanako Imasaki; Yoshihiro Kohara; Daiki Yatsushiro; Daiki Atarashi; Makoto Handa; Yusuke Kataoka (Crystals, 2020)
A novel heteroleptic paddlewheel-type dirhodium (Rh2) complex [Rh2(O2CCH3)3(PABC)] (1; PABC = para-aminobenzenecarboxylate), which has an amino group as a potential donor site for coordination with the metal ion, was synthesized and characterized by 1H NMR, ESI-TOF-MS, infrared spectra, and elemental analysis. The slow evaporation of N,N-dimethylformamide (DMF)-dissolved 1 produces the purple-colored crystalline polymeric species [Rh2(O2CCH3)3 (PABC)(DMF)]n (1P). Single-crystal and powder X-ray diffraction analyses, as well as thermo-gravimetric analysis, clarified that 1P formed a one-dimensional polymeric structure, in which the two axial sites of the Rh2 ion in 1P are coordinated by a DMF molecule and an amino group of the PABC ligand of the neighboring molecule 1, by coordination-induced self-assembly (polymerization) with an Rh-amino bond. The reversible structural change (self-assembly and disassembly transformations) between the discrete species [Rh2(O2CCH3)3(PABC)(DMF)2] (1D; green solution) and the polymeric species 1P (purple solid) was accompanied by a color change, which easily occurred by the dissolution and evaporation procedures with DMF.